Improving Goal Concordant Care Among 10 Leading Academic U.S. Cancer Hospitals: A Collaboration of the Alliance of Dedicated Cancer Centers. (15th June 2021) - McNiff, Kristen K.; Caligiuri, Michael A.; Davidson, Nancy E.; Farrar, William; Fisher, Richard I.; Glimcher, Laurie H.; Hanners, Rodney B.; Hwu, Patrick; Johnson, Candace S.; Pisters, Peter W.T.; Thompson, Craig B.; Reddy, Akhila S.; et al.
Abstract : This commentary is a call to action: that all patients with cancer and their families should receive care that aligns with their values and unique priorities. This is the vision of the Improving Goal Concordant Care (IGCC) Initiative, convened by the Alliance of Dedicated Cancer Centers (ADCC).